2023
DOI: 10.3390/children10020400
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Automated Atrial CMR Measures and a Novel Atrioventricular Coupling Index for Predicting Risk in Repaired Tetralogy of Fallot

Abstract: Atrial size and function have been recognized as markers of diastolic function, and diastolic dysfunction has been identified as a predictor of adverse outcomes in repaired tetralogy of Fallot (rTOF). This was a retrospective single-center study with the objective of investigating the use of atrial measurements obtained via CMR for predicting outcomes in rTOF patients. Automated contours of the left and right atria (LA and RA) were performed. A novel parameter, termed the Right Atrioventricular Coupling Index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…Despite these advantages of 3D over 2D echocardiography, our study is the first assessment of atrioventricular coupling using 3D echocardiography. So far, the only other evaluation of RACI was undertaken using CMR in a cohort of pediatric patients with repaired tetralogy of Fallot, and it showed that CMR-derived RACI was a predictor of malignant arrhythmias [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these advantages of 3D over 2D echocardiography, our study is the first assessment of atrioventricular coupling using 3D echocardiography. So far, the only other evaluation of RACI was undertaken using CMR in a cohort of pediatric patients with repaired tetralogy of Fallot, and it showed that CMR-derived RACI was a predictor of malignant arrhythmias [12].…”
Section: Discussionmentioning
confidence: 99%
“…Although three-dimensional (3D) LV and LA volumes showed a good correlation with CMR measurements [11], LACI has not been assessed so far using 3D echocardiography, and its utility in DCM is unknown. There is no data regarding the 3D right atrioventricular coupling index (RACI), defined as the ratio between RA EDV and RV EDV [12]. Therefore, the aim of our study was to assess, through 3D echocardiography, the prognostic role of LACI, RACI and a novel combined atrioventricular coupling index (CACI) in patients with DCM.…”
Section: Introductionmentioning
confidence: 99%